2015
DOI: 10.1371/journal.pone.0136695
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Hepcidin Levels in Iron-Deficient and Iron-Supplemented Piglets Correlate with Hepcidin Hepatic mRNA and Serum Levels and with Body Iron Status

Abstract: Among livestock, domestic pig (Sus scrofa) is a species, in which iron metabolism has been most intensively examined during last decade. The obvious reason for studying the regulation of iron homeostasis especially in young pigs is neonatal iron deficiency anemia commonly occurring in these animals. Moreover, supplementation of essentially all commercially reared piglets with iron entails a need for monitoring the efficacy of this routine practice followed in the swine industry for several decades. Since the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…However, routinely applied dose of 200 mg Fe per piglet in the form of a single intramuscular injection of FeDex seems not being efficiently metabolized and detoxified [8]. Moreover, we have previously reported that high iron parenteral supplementation with FeDex induces expression of hepcidin (Hepc) [8,12,13], a 25-amino acid peptide hormone, the master regulator of the systemic iron homeostasis in vertebrates [14]. It is well established that high Hepc may perturb body iron homeostasis by inhibiting both duodenal iron absorption and iron recycling by macrophages of the reticuloendothelial system (RES) that catabolize heme contained in phagocytosed senescent RBC [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, routinely applied dose of 200 mg Fe per piglet in the form of a single intramuscular injection of FeDex seems not being efficiently metabolized and detoxified [8]. Moreover, we have previously reported that high iron parenteral supplementation with FeDex induces expression of hepcidin (Hepc) [8,12,13], a 25-amino acid peptide hormone, the master regulator of the systemic iron homeostasis in vertebrates [14]. It is well established that high Hepc may perturb body iron homeostasis by inhibiting both duodenal iron absorption and iron recycling by macrophages of the reticuloendothelial system (RES) that catabolize heme contained in phagocytosed senescent RBC [15].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize both toxicity of supplemental iron and its capacity to induce hepcidin synthesis, we proposed several modifications of routine procedure of FeDex administration to piglets [8,12]. Furthermore, considering that heme preparations have been successfully used to prevent and treat IDA in humans [16][17][18], dogs [19], and pigs [20,21], we used bovine hemoglobin as heme iron supplement.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the incidence of such risk has been clearly demonstrated in iron-supplemented women showing significantly decreased fractional iron absorption, which was associated with acute increase in hepcidin [57]. In our studies we have performed for the first time a comprehensive analysis of hepcidin expression (we measured the abundance of hepcidin mRNA in the liver as well as hepcidin concentration in blood plasma and urine) in suckling piglets supplemented with FeDex and in anemic, nonsupplemented animals [16,17,58]. Administration of large amounts of iron to piglets resulted in a significant increase in hepcidin expression, which appears immediately (only one day) after the injection of FeDex and is sustained at high level up to weaning (day 28 after birth).…”
Section: Intramuscular Supplementation With Iron Dextran (Fedex) -A Gmentioning
confidence: 99%
“…Nevertheless, there is a general consensus regarding hemoglobin concentration to set the cutoff level of anemia in suckling piglets at 8g/dL [12,13] although some authors claim about higher values reaching 11-13 g/dL [14]. It is clear from many studies [15][16][17][18][19][20] including our own [15][16][17] that such level of Hgb is reachable only in piglets supplemented with very high doses of iron. Without iron supplementation IDA in piglets appears few days after birth.…”
Section: Iron Deficiency Anemia (Ida) In Suckling Pigletsmentioning
confidence: 99%
See 1 more Smart Citation